TEACHING PRE-SCHOOL CHILDREN BY REALIA (ResearchJet Journal of Analysis and Inventions, 2021)
This article has been written to describe the process of teaching English language, especially, initial vocabulary source, using some educational ways which are usually known as realia, to find out the difficulties of teaching words to the pre-school students by using real objects and with the help of them to solve the problems found out in order to make the teaching and learning process much better. In addition, in this paper one can absorb information about benefits of using real objects in teaching classes and how to use them.